Optical film
By using (meth)acrylic resin film with high glass transition temperature and crosslinked particles, combined with the design of an easy-to-adhesive layer, the damage problem of optical film during winding is solved, the balance of anti-adhesion and optical properties is achieved, and the stability and function of the optical film are improved.
Patent Information
- Application Number
- CN202510174865.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-21
- Filing Date
- 2025-02-18
- Publication Date
- 2025-08-22
AI Technical Summary
The existing optical films are easily damaged by film contact during winding, and the aggregation of lubricating particles affects transparency and uniformity, making it difficult to have both anti-adhesion and good optical properties.
A (meth)acrylic resin film with a glass transition temperature of 120°C or above is used to combine crosslinked particles and an easy-to-adhesive layer to control the content of lubricating particles and Young's modulus to ensure that the static friction coefficient is within a suitable range, and a surface concave and convex structure is formed to improve the resistance to adhesion.
It realizes that the optical film has good anti-adhesion properties without damaging transparency and uniformity, reduces film damage, and improves the smoothness and functional stability of the optical film.
Smart Images

Figure CN120518907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to optical films. Background Art
[0002] Optical films such as polarizer protective films require optical transparency, optical uniformity, and smoothness. Cellulose films have been commonly used as polarizer protective films in the past, but in recent years, (meth)acrylic resin films have been used to improve durability. Furthermore, to improve adhesion to polarizers, an easy-adhesion layer-forming composition is applied to the surface of a (meth)acrylic resin film to form an easy-adhesion layer.
[0003] When these optical films are wound into a roll, they may come into contact with each other, causing damage, unevenness, etc. Therefore, to prevent such damage and unevenness, it has been proposed to add lubricating particles having anti-blocking properties, such as silica particles having a specific particle size, to the adhesion layer to improve the smoothness of the optical film (see, for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2020-52944 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] However, lubricating particles such as silica particles tend to aggregate in the adhesive layer-forming composition, making it difficult to evenly distribute the lubricating particles on the surface of the (meth)acrylic resin film, preventing the full development of anti-blocking properties. Furthermore, the aggregation of lubricating particles can sometimes affect the transparency and other functions of the optical film.
[0009] Therefore, an object of the present invention is to provide an optical film having anti-blocking properties without impairing its function as an optical film.
[0010] Solutions for solving problems
[0011] Specific means for solving the above-mentioned problems include the following embodiments.
[0012] <1> An optical film comprising a (meth)acrylic resin film and an easily adhesive layer formed on the (meth)acrylic resin film, wherein the (meth)acrylic resin film contains a (meth)acrylic resin as a main component and crosslinked particles, and the optical film satisfies the following conditions.
[0013] (i) the glass transition temperature of the (meth)acrylic resin film is 120° C. or higher,
[0014] (ii) the Young's modulus of the composition for forming the easily adhesive layer when formed into a sheet having a thickness of 100 μm is 1.0 GPa or more and 2.5 GPa or less,
[0015] (iii) the content of the lubricating particles in the easy-adhesion layer is 0.1% by weight or less,
[0016] (iv) The total value of the ten-point average roughness Rzjis of the surface of the easily adhesive layer and the ten-point average roughness Rzjis of the surface of the (meth)acrylic resin film on the opposite side to the easily adhesive layer is 23 nm to 200 nm.
[0017] <2> according to <1> In the optical film, the thickness of the easy-adhesion layer is not less than 50 nm and not more than 600 nm.
[0018] <3> according to <1> or <2> The optical film, wherein when two optical films are stacked such that the (meth)acrylic resin film and the easily adhesive layer are in contact, the static friction coefficient measured in accordance with JIS K 7125:1999 is 0.3 or more and 1.5 or less.
[0019] <4> according to <1> ~ <3> The optical film according to any one of the preceding claims, wherein the (meth)acrylic resin film comprises a (meth)acrylic resin having a ring structure in its main chain.
[0020] <5> according to <4> In the optical film, the ring structure is at least one selected from the group consisting of a glutarimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure.
[0021] <6> according to <4> or <5> The optical film is characterized in that the (meth)acrylic resin having a ring structure in its main chain contains a structural unit represented by the following general formula (1).
[0022]
[0023] (Where R 1 and R 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
[0024] <7> according to <6> The optical film is characterized in that the ratio of the structural unit represented by the general formula (1) in the (meth)acrylic resin having a ring structure in the main chain is 2% by weight or more and 30% by weight or less.
[0025] <8> according to <1> ~ <7> The optical film according to any one of the preceding claims, wherein the (meth)acrylic resin film contains an aromatic vinyl unit.
[0026] <9> according to <4> ~ <7> The optical film according to any one of the preceding claims, wherein the (meth)acrylic resin film further comprises a copolymer containing an aromatic vinyl unit.
[0027] <10> according to <9> In the optical film, the copolymer further comprises a (meth)acrylate unit or a (meth)acrylonitrile unit.
[0028] <11> A composition for forming an easy-adhesion layer, which is used to form an easy-adhesion layer on a (meth)acrylic resin film.
[0029] The (meth)acrylic resin film comprises a (meth)acrylic resin as a main component, contains crosslinked particles, and has a glass transition temperature of 120° C. or higher.
[0030] The content of the lubricating particles in the easily adhesive layer-forming composition is 0.1% by weight or less.
[0031] The Young's modulus of the easily-adhesive layer-forming composition when formed into a sheet having a thickness of 100 μm is 1.0 GPa or more and 2.5 GPa or less.
[0032] <12> according to <11> In the composition for forming an easily adhesive layer, the (meth)acrylic resin film includes a (meth)acrylic resin having a ring structure in its main chain.
[0033] <13> according to <12> In the composition for forming an easily adhesive layer, the ring structure is at least one selected from the group consisting of a glutarimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure.
[0034] <14> according to <12> or <13> In the composition for forming an easily adhesive layer, the (meth)acrylic resin having a ring structure in its main chain contains a structural unit represented by the following general formula (1).
[0035]
[0036] (Where R 1 and R 2Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
[0037] <15> according to <14> The composition for forming an easily adhesive layer is characterized in that the ratio of the structural unit represented by the general formula (1) in the (meth)acrylic resin having a ring structure in its main chain is 2% by weight or more and 30% by weight or less.
[0038] Effects of the Invention
[0039] According to the present invention, an optical film having anti-blocking properties can be provided without impairing the function of the optical film. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic cross-sectional view of the optical film according to this embodiment.
[0041] Description of Reference Numerals
[0042] 1 Optical Film
[0043] 2 Easy-adhesion layer
[0044] 3 (Meth) acrylic resin film
[0045] 4 Cross-linked particles DETAILED DESCRIPTION
[0046] The following describes one embodiment of the present invention, but the present invention is not limited to this embodiment. In this specification, the term "(meth)acrylic" refers to both "acrylic" and "methacrylic." The same applies to terms such as "(meth)acryloyl," "(meth)acrylic acid," and "(meth)acrylonitrile."
[0047] <Optical Film>
[0048] The optical film according to this embodiment includes a (meth)acrylic resin film containing a (meth)acrylic resin as a main component and crosslinked particles, and an easily adhesive layer formed on the (meth)acrylic resin film.
[0049] Here, the term "(meth)acrylic resin" refers to a resin in which the proportion of structural units derived from a polymerizable monomer having a (meth)acryloyl group is 50% by weight or greater. Furthermore, "(meth)acrylic resin as the main component" means that the content of the (meth)acrylic resin in the (meth)acrylic resin film is 50% by weight or greater.
[0050] A schematic cross-sectional view of the optical film according to this embodiment is shown in FIG. Figure 1 . Figure 1 The illustrated optical film 1 includes a (meth)acrylic resin film 3 containing crosslinked particles 4, and an easily adhesive layer 2 formed on the (meth)acrylic resin film 3. The inclusion of the crosslinked particles 4 in the (meth)acrylic resin film 3 creates irregularities on the surface of the (meth)acrylic resin film 3. Since the easily adhesive layer 2 is formed on the irregularities of the (meth)acrylic resin film 3, irregularities also appear on the surface of the easily adhesive layer 2. As a result, the optical film 1 exhibits anti-blocking properties.
[0051] Regarding the optical film according to this embodiment, when two optical films are stacked such that the (meth)acrylic resin film and the easily adhesive layer are in contact, the static friction coefficient measured in accordance with JIS K 7125:1999 is preferably 0.3 or more and 1.5 or less, more preferably 0.4 or more and 1.3 or less, and even more preferably 0.4 or more and 1.2 or less. When the static friction coefficient between the (meth)acrylic resin film and the easily adhesive layer is within the above range, there is a tendency for good anti-blocking properties to be exhibited.
[0052] [(Meth)acrylic resin film]
[0053] The (meth)acrylic resin film forms the substrate of the optical film and contains a (meth)acrylic resin as a main component. The (meth)acrylic resin content in the (meth)acrylic resin film is preferably 50% by weight or greater, more preferably 60% by weight or greater, even more preferably 70% by weight or greater, and particularly preferably 75% by weight or greater.
[0054] As the (meth)acrylic resin, any appropriate (meth)acrylic resin can be used. Specific examples include poly(meth)acrylates (e.g., polymethyl methacrylate), methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-acrylate-(meth)acrylic acid copolymers, methyl (meth)acrylate-styrene copolymers, and polymers having alicyclic hydrocarbon groups (e.g., methyl methacrylate-cyclohexyl methacrylate copolymers, methyl methacrylate-norbornyl (meth)acrylate copolymers). Among these, poly(meth)acrylic acid C1-C6 alkyl esters (poly(meth)acrylate resins having an alkyl group with 1 to 6 carbon atoms) such as polymethyl (meth)acrylate are preferred, and poly(methyl methacrylate resins having methyl methacrylate as the main component (50% by weight or more, preferably 70% by weight or more) are more preferred.
[0055] The (meth)acrylic resin film may contain aromatic vinyl units. The aromatic vinyl units may constitute the (meth)acrylic resin as the main component, or may constitute a resin different from the (meth)acrylic resin as the main component. The content of the aromatic vinyl units in the (meth)acrylic resin film is preferably from 0% by weight to 25% by weight, more preferably from more than 0% by weight to 25% by weight, and even more preferably from 0.5% by weight to 20% by weight.
[0056] (Meth)acrylic resin films have heat resistance and durability, and have a glass transition temperature of 120°C or higher. The glass transition temperature of a (meth)acrylic resin film is preferably higher than 120°C, more preferably higher than 121°C, and even more preferably higher than 122°C. When the glass transition temperature of a (meth)acrylic resin film is higher than 120°C, the film's dimensional change rate in high-temperature environments tends to decrease. In actual use, (meth)acrylic resin films are often laminated with other films. In such cases, a low dimensional change rate can suppress deformation and warping caused by differences in dimensional change rate between the film and the other laminated film.
[0057] The glass transition temperature can be determined by measuring the temperature at a heating rate of 20° C. / min in a nitrogen atmosphere using a differential scanning calorimeter (DSC7000X, manufactured by Hitachi High-Technologies Corporation) and by a midpoint method.
[0058] ((Meth)acrylic resin having a ring structure in the main chain)
[0059] In the (meth)acrylic resin film, as a (meth)acrylic resin having a glass transition temperature of 120°C or higher, a (meth)acrylic resin having a ring structure in the main chain is preferably included. Examples of the ring structure include at least one ring structure selected from the group consisting of a glutarimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure. Of these, a (meth)acrylic resin having a glutarimide structure or a lactone ring structure in the main chain is preferred. From the perspectives of ease of production, cost, and quality stability in moisture, a (meth)acrylic resin having a glutarimide structure in the main chain is more preferred.
[0060] The ratio of the ring structure in the (meth)acrylic resin having a ring structure in the main chain is not particularly limited, but is, for example, from 1% to 80% by weight, preferably from 2% to 30% by weight. A high ratio of the ring structure within this range is preferred from the perspective of increasing the glass transition temperature, while a low ratio of the ring structure within this range is preferred from the perspective of reducing the phase difference.
[0061] Each ring structure is described below.
[0062] The (meth)acrylic resin having a glutarimide structure in the main chain is, for example, a resin having a glutarimide unit represented by the following general formula (1) and a methyl methacrylate unit, and can be produced by heating and melting a polymethyl methacrylate resin and then treating it with an imidizing agent.
[0063]
[0064] (Where R 1 and R 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
[0065] The proportion of glutarimide units in the (meth)acrylic resin having a glutarimide structure in the main chain is preferably 2% by weight or more and 30% by weight or less. When the proportion of glutarimide units is 2% by weight or more, desired heat resistance tends to be easily imparted. Furthermore, when the proportion of glutarimide units is 30% by weight or less, the amount of imidizing agent added can be reduced, and odor caused by residual volatile components can be suppressed, thereby tending to reduce the thickness direction retardation Rth.
[0066] In the above general formula (1), R 3 When is a methyl group, the ratio of the glutarimide unit can be measured by, for example, the following method. 1 H-NMR BRUKER Avance III (400 MHz) was used to analyze the resin 1 H-NMR measurement. The molar ratio is calculated based on the peak area A of the protons originating from O—CH3 constituting methyl methacrylate near 3.5 ppm to 3.8 ppm and the peak area B of the protons originating from N—CH3 constituting the glutarimide ring near 3.0 ppm to 3.3 ppm. By converting this molar ratio to weight, the proportion of glutarimide units can be calculated.
[0067] When producing polymethyl methacrylate resin, in addition to methyl methacrylate, other monomers such as methyl acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, benzyl (meth)acrylate, and cyclohexyl (meth)acrylate may be used in combination. Furthermore, in addition to the above monomers, nitrile monomers such as acrylonitrile and methacrylonitrile; maleimide monomers such as maleimide, N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; and aromatic vinyl monomers such as styrene and α-methylstyrene may also be used in combination. The proportion of acrylate units in the polymethyl methacrylate resin is preferably less than 1% by weight. In particular, the proportion of methyl acrylate units is preferably less than 0.5% by weight, and more preferably less than 0.3% by weight.
[0068] The structure of the polymethyl methacrylate resin is not particularly limited, and may be any of a linear (linear) polymer, a block polymer, a core-shell polymer, a branched polymer, a ladder polymer, a cross-linked polymer, and the like.
[0069] The manufacture method of polymethyl methacrylate resin is not particularly limited, and known emulsion polymerization, emulsification-suspension polymerization, suspension polymerization, bulk polymerization, solution polymerization etc. can be adopted. When being used in the field of optics, from the viewpoint that impurities decrease, bulk polymerization and solution polymerization are preferably used. Polymethyl methacrylate resin can be manufactured according to the method for recording in, for example, Japanese Unexamined Patent Publication No. 56-8404, Japanese Special Publication No. 6-86492, Japanese Special Publication No. 7-37482, Japanese Special Publication No. 52-32665 etc.
[0070] The method for producing a (meth)acrylic resin having a glutarimide structure in its main chain includes a step of heating and melting the polymethyl methacrylate resin and then treating the resin with an imidizing agent (imidization step).
[0071] The imidizing agent is not particularly limited as long as it can generate the glutarimide unit represented by the general formula (1), and substances described in International Publication No. 2005 / 054311 can be used. Specifically, examples of the imidizing agent include amines containing aliphatic hydrocarbon groups such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, and n-hexylamine; amines containing aromatic hydrocarbon groups such as aniline, benzylamine, toluidine, and trichloroaniline; and amines containing alicyclic hydrocarbon groups such as cyclohexylamine. Among these, methylamine, ammonia, and cyclohexylamine are preferred from the perspective of cost and physical properties, and methylamine is more preferred. It should be noted that methylamine, which is gaseous at room temperature, can be used in a state dissolved in an alcohol such as methanol.
[0072] In the imidization step, the ratio of glutarimide units to (meth)acrylate units in the resulting (meth)acrylic resin can be adjusted by adjusting the amount of the imidizing agent added. Furthermore, by adjusting the degree of imidization, the physical properties of the resulting (meth)acrylic resin and the optical properties of a (meth)acrylic resin film formed from the (meth)acrylic resin can be adjusted.
[0073] The amount of the imidizing agent added is preferably 0.5 parts by weight or more and 20 parts by weight or less relative to 100 parts by weight of the polymethyl methacrylate resin. If the amount of the imidizing agent added is 0.5 parts by weight or more, the proportion of glutarimide units increases, resulting in improved heat resistance of the (meth)acrylic resin and a tendency to prevent appearance defects after molding. Furthermore, if the amount of the imidizing agent added is 20 parts by weight or less, the imidizing agent tends to be less likely to remain in the (meth)acrylic resin, preventing appearance defects and foaming after molding.
[0074] In addition, in the imidization step, a ring closure accelerator (catalyst) may be added in addition to the imidization agent.
[0075] The method of heating and melting the polymethyl methacrylate resin and treating it with an imidizing agent is not particularly limited, and any conventionally known method can be employed. For example, the polymethyl methacrylate resin can be imidized by using an extruder, a batch reaction tank (pressure vessel), or the like.
[0076] Use extruder by polymethyl methacrylate resin heating and melting, and when utilizing imidizing agent to process, as extruder, various extruders such as single screw extruder, twin screw extruder, multi-screw extruder can be used.Among these, preferably use twin screw extruder.If utilize twin screw extruder, then can promote the mixing of imidizing agent (when using ring closure accelerator, be imidizing agent and ring closure accelerator) and polymethyl methacrylate resin.
[0077] Examples of twin-screw extruders include non-intermeshing co-rotating, intermeshing co-rotating, non-intermeshing counter-rotating, and intermeshing counter-rotating types, with intermeshing co-rotating types being preferred. Intermeshing co-rotating twin-screw extruders can rotate at high speeds, thereby further promoting mixing of the imidizing agent (and the ring-closing accelerator when a ring-closing accelerator is used) with the polymethyl methacrylate resin.
[0078] The extruders exemplified above may be used alone or in series. For example, a tandem-type reaction extruder described in Japanese Patent Application Laid-Open No. 2008-273140 may be used.
[0079] When the imidization reaction is carried out in an extruder, for example, polymethyl methacrylate resin is fed from the raw material feeding portion of the extruder, the resin is melted and filled in the cylinder, and then the imidization agent is injected into the extruder using an addition pump.
[0080] In this case, it is preferred to set the temperature of the reaction zone in the extruder (resin temperature) to 180°C or higher and 270°C or lower, more preferably to 200°C or higher and 250°C or lower. If the temperature of the reaction zone (resin temperature) is 180°C or higher, there is a tendency for the imidization reaction to proceed sufficiently and for the heat resistance to be improved. In addition, if the temperature of the reaction zone is 270°C or lower, the decomposition of the resin can be suppressed, and as a result, there is a tendency for the reduction in the bending resistance of the film formed from the obtained (meth) acrylic resin to be suppressed. Here, the reaction zone in the extruder refers to the region between the injection position of the imidization agent and the resin ejection port (die portion) in the barrel of the extruder.
[0081] By extending the reaction time in the reaction zone of the extruder, imidization can be further advanced. The reaction time in the reaction zone of the extruder is preferably more than 10 seconds, more preferably more than 30 seconds. If the reaction time is less than 10 seconds, there is a possibility that imidization will hardly proceed.
[0082] The resin pressure in the extruder is preferably set to more than atmospheric pressure and below 50MPa, more preferably set to more than 1MPa and below 30MPa. If the resin pressure is more than 1MPa, there is a tendency that the solubility of the imidizing agent is improved and the reaction is further carried out. In addition, if the resin pressure is below 50MPa, no special device is required, which is preferred in terms of cost.
[0083] When using an extruder, it is preferable to install a vent hole capable of reducing the pressure to below atmospheric pressure in order to remove unreacted imidization agent, by-products such as methanol, monomers, and the like.
[0084] In addition, a horizontal twin-screw reactor such as BIVOLAK manufactured by Sumitomo Heavy Industries, Ltd. or a vertical twin-screw stirring tank such as SUPERBLEND that can cope with high viscosity can also be suitably used instead of the extruder.
[0085] When polymethyl methacrylate resin is heated and melted using a batch reaction tank (pressure vessel) and processed using an imidizing agent, the structure of the batch reaction tank is not particularly limited. As a batch reaction tank, as long as there is a structure in which polymethyl methacrylate resin can be melted and stirred by heating, an imidizing agent (when a ring-closure accelerator is used, an imidizing agent and a ring-closure accelerator) can be added, it is preferred to have a structure with good stirring efficiency. Utilizing this batch reaction tank, it is possible to prevent the polymer viscosity from rising due to reacting, and stirring becomes insufficient. As the batch reaction tank with this structure, for example, the stirred tank MAXBLEND manufactured by Sumitomo Heavy Industries, Ltd. can be listed.
[0086] Specific examples of the imidization method include known methods described in, for example, JP-A-2008-273140 and JP-A-2008-274187.
[0087] In the method for producing a (meth)acrylic resin having a glutarimide structure in its main chain, in addition to the imidization step, a step of treating the resin with an esterifying agent (esterification step) may be further included. The acid value of the imidized resin obtained in the imidization step can be adjusted to a desired range through the esterification step.
[0088] Examples of the esterifying agent include dimethyl carbonate, 2,2-dimethoxypropane, dimethyl sulfoxide, triethyl o-formate, trimethyl o-acetate, trimethyl o-formate, diphenyl carbonate, dimethyl sulfate, methyl toluenesulfonate, methyl trifluoromethylsulfonate, methyl acetate, methanol, ethanol, methyl isocyanate, p-chlorophenyl isocyanate, dimethylcarbodiimide, dimethyl-tert-butylsilyl chloride, isopropylene acetate, dimethylurea, tetramethylammonium hydroxide, dimethyldiethoxysilane, tetra-N-butoxysilane, dimethyl (trimethylsilyl) phosphite, trimethyl phosphite, trimethyl phosphate, tricresyl phosphate, diazomethane, ethylene oxide, propylene oxide, cyclohexane oxide, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, and benzyl glycidyl ether. Among these, dimethyl carbonate and trimethyl o-acetate are preferred from the viewpoint of cost, reactivity, and the like, and dimethyl carbonate is more preferred from the viewpoint of cost.
[0089] The amount of the esterifying agent added is preferably from 0 to 12 parts by weight, more preferably from 0 to 8 parts by weight, relative to 100 parts by weight of the polymethyl methacrylate resin. When the amount of the esterifying agent is within the above range, the acid value can be adjusted to an appropriate range, and unreacted esterifying agent tends to be less likely to remain in the resin.
[0090] In the esterification step, a catalyst may be used in combination with an esterifying agent. Examples of the catalyst include aliphatic tertiary amines such as trimethylamine, triethylamine, and tributylamine. Among these, triethylamine is preferred from the perspectives of cost and reactivity.
[0091] It should be noted that in the esterification step, heat treatment alone may be performed without using an esterifying agent. When heat treatment alone (mixing and dispersion of the molten resin in the extruder) is performed, at least a portion of the carboxyl groups generated in the imidization step can be converted to anhydride groups through dehydration reactions between the carboxyl groups and the alkyl ester groups, dealcoholization reactions between the carboxyl groups, and the like. In this case, a ring closure accelerator (catalyst) may also be used. Even when using an esterifying agent, heat treatment can be used to convert the carboxyl groups to anhydride groups.
[0092] The (meth)acrylic resin having a lactone ring structure in its main chain is not particularly limited as long as it is a thermoplastic polymer having a lactone ring structure in its molecule (a thermoplastic polymer having a lactone ring structure introduced into its molecular chain). There are no particular limitations on its production method. Preferably, it is obtained by polymerizing to obtain a polymer having hydroxyl groups and ester groups in its molecular chain (polymerization step), followed by heating the resulting polymer to introduce a lactone ring structure into the polymer (lactone cyclocondensation step).
[0093] In the polymerization step, a polymerization reaction of monomer components including an unsaturated monomer represented by the following general formula (2) is carried out to obtain a polymer having a hydroxyl group and an ester group in the molecular chain.
[0094]
[0095] (Where R 4 and R 5 Each independently represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.)
[0096] Examples of the unsaturated monomer represented by the general formula (2) include methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, and tert-butyl 2-(hydroxymethyl)acrylate. Among these, methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate are preferred, and methyl 2-(hydroxymethyl)acrylate is more preferred from the perspective of achieving a high effect of improving heat resistance. These unsaturated monomers may be used alone or in combination of two or more.
[0097] The content of the unsaturated monomer represented by the general formula (2) in the monomer component is preferably 5% by weight or more and 50% by weight or less, more preferably 10% by weight or more and 40% by weight or less, and further preferably 10% by weight or more and 30% by weight or less. If the content of the unsaturated monomer represented by the general formula (2) is 5% by weight or more, there is a tendency for the heat resistance, solvent resistance, surface hardness, etc. of the resulting resin to be improved. In addition, if the content of the unsaturated monomer represented by the general formula (2) is 50% by weight or less, there is a tendency that the cross-linking reaction and gelation that occur when the lactone ring structure is formed can be suppressed, and the reduction in fluidity can be suppressed. In addition, there is a tendency that the further condensation reaction, the generation of volatile substances, the generation of silver streaks, and the increase in thickness direction phase difference Rth during molding due to the remaining unreacted hydroxyl groups can be suppressed.
[0098] The monomer components may contain other monomers in addition to the unsaturated monomer represented by the general formula (2). Examples of the other monomers include (meth)acrylates, hydroxyl-containing monomers, unsaturated carboxylic acids, and unsaturated monomers represented by the general formula (3). The other monomers may be used alone or in combination of two or more.
[0099]
[0100] (Where R 6 represents a hydrogen atom or a methyl group, and X represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group, an -OAc group, a -CN group, or a -CO-R 7 Ac represents acetyl, R 7 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.)
[0101] The (meth)acrylate is not particularly limited as long as it is an unsaturated monomer other than the unsaturated monomer represented by the general formula (2). Examples thereof include acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, cyclohexyl acrylate, and benzyl acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate. Among these, methyl methacrylate is preferred from the viewpoint of heat resistance and transparency.
[0102] When (meth)acrylate is used, the content of (meth)acrylate in the monomer component is preferably 10% by weight or more and 95% by weight or less, more preferably 10% by weight or more and 90% by weight or less, further preferably 40% by weight or more and 90% by weight or less, and particularly preferably 50% by weight or more and 90% by weight or less.
[0103] (Copolymer containing aromatic vinyl units)
[0104] The (meth)acrylic resin film may contain, in addition to the (meth)acrylic resin having a ring structure in the main chain, a copolymer containing an aromatic vinyl unit. Examples of the copolymer containing an aromatic vinyl unit include (meth)acrylate-aromatic vinyl copolymers such as methyl methacrylate-styrene copolymers; and (meth)acrylonitrile-aromatic vinyl copolymers such as acrylonitrile-styrene copolymers.
[0105] Examples of the aromatic vinyl group include styrene, α-methylstyrene, methoxystyrene, vinyltoluene, and halogenated styrene. Among these, styrene is preferred.
[0106] Examples of (meth)acrylates include acrylates such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, cyclohexyl acrylate, and benzyl acrylate; and methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate. Among these, methyl methacrylate is preferred.
[0107] The proportion of aromatic vinyl units in the (meth)acrylate-aromatic vinyl copolymer is preferably from 10% by weight to 30% by weight, more preferably from 15% by weight to 28% by weight. When the proportion of aromatic vinyl units is within this range, the transparency of the (meth)acrylic resin film tends to be maintained.
[0108] The ratio of (meth)acrylonitrile units in the (meth)acrylonitrile-aromatic vinyl copolymer is preferably 22% by weight or more and 28% by weight or less, and more preferably 23% by weight or more and 27% by weight or less. When the ratio of (meth)acrylonitrile units is within the above range, the transparency of the (meth)acrylic resin film tends to be maintained.
[0109] The content of the aromatic vinyl unit-containing copolymer in the (meth)acrylic resin film is, for example, preferably from 0% by weight to 30% by weight, and more preferably from 3% by weight to 25% by weight.
[0110] (Other thermoplastic resins)
[0111] The (meth)acrylic resin film may contain other thermoplastic resins in addition to the above-mentioned ones. Examples of other thermoplastic resins include olefin polymers, halogenated vinyl polymers, styrene polymers, ester polymers, and amide polymers.
[0112] The content of other thermoplastic resins in the (meth)acrylic resin film is, for example, preferably from 0% by weight to 50% by weight, and more preferably from 0% by weight to 30% by weight.
[0113] The smaller the orientation birefringence of the (meth)acrylic resin film, the better. The orientation birefringence is preferably -1.7×10 -4 Above and 1.7×10 -4 When the orientation birefringence is within the above range, the retardation value of the (meth)acrylic resin film tends to be small.
[0114] In addition, the smaller the photoelastic coefficient of the (meth)acrylic resin film, the better, the photoelastic coefficient is preferably -10×10 -12 Pa -1 Above and 10×10 -12 Pa -1 Below, more preferably -4×10 -12 Pa -1 Above and 4×10 -12 Pa -1 the following.
[0115] (cross-linked particles)
[0116] By incorporating crosslinked particles into the (meth)acrylic resin film, irregularities are formed on the surface of the (meth)acrylic resin film. Since the easily adhesive layer is formed on the surface of the (meth)acrylic resin film having irregularities, irregularities also appear on the surface of the easily adhesive layer, thereby achieving anti-blocking properties.
[0117] Examples of the crosslinked particles include crosslinked acrylic resin particles, crosslinked polystyrene resin particles, melamine resin particles, and crosslinked silicone resin particles. Among these, crosslinked acrylic resin particles are preferred from the viewpoints of compatibility with (meth)acrylic resins, dispersibility, transparency, and the like.
[0118] The monomers forming the crosslinked acrylic resin particles can be selected from any (meth)acrylates and other monomers copolymerizable with (meth)acrylates. Among these, methyl methacrylate is preferred from the perspectives of compatibility with the (meth)acrylic resin and refractive index. In this case, the proportion of methyl methacrylate units in the crosslinked acrylic resin particles is preferably 70% by weight or more and 99% by weight or less, and more preferably 80% by weight or more and 99% by weight or less.
[0119] The crosslinked acrylic resin particles further include a structural unit derived from a polyfunctional monomer having two or more polymerizable groups in the molecule. The proportion of the polyfunctional monomer unit in the crosslinked acrylic resin particles is preferably 0.5% by weight or more and 30% by weight or less.
[0120] When the refractive index of the (meth)acrylic resin is set to 100%, the refractive index of the crosslinked particles is preferably 98% to 102%, more preferably 99% to 101%. The refractive index of the crosslinked particles is preferably 1.47 to 1.55, more preferably 1.47 to 1.53, and even more preferably 1.48 to 1.52. Using crosslinked particles with a refractive index within this range tends to produce a (meth)acrylic resin film with high transparency. Crosslinked acrylic resin particles are preferred because they meet the above refractive index.
[0121] From the perspective of imparting anti-blocking properties, the average particle size of the cross-linked particles is preferably 0.1 μm to 2.5 μm, more preferably 0.3 μm to 2.0 μm, even more preferably 0.5 μm to 2.0 μm, and particularly preferably 0.5 μm to 1.5 μm. When the average particle size of the cross-linked particles is 0.1 μm or greater, there is a tendency to form irregularities on the surface of the (meth)acrylic resin film, thereby imparting anti-blocking properties to the easily adhesive layer formed on the surface of the (meth)acrylic resin film. Furthermore, when the average particle size of the cross-linked particles is 2.5 μm or less, there is a tendency to maintain the optical properties required of the optical film without compromising the surface smoothness of the optical film.
[0122] The content of crosslinked particles in the (meth)acrylic resin film is preferably 0.01% by weight or more and 1.0% by weight or less, more preferably 0.03% by weight or more and 0.7% by weight or less, further preferably 0.05% by weight or more and 0.5% by weight or less, particularly preferably 0.08% by weight or more and 0.4% by weight or less, and extremely preferably 0.08% by weight or more and 0.2% by weight or less, based on the weight of the (meth)acrylic resin film. A crosslinked particle content of 0.01% by weight or more tends to provide sufficient windability. Furthermore, a crosslinked particle content of 1.0% by weight or less tends to maintain the transparency of the (meth)acrylic resin film.
[0123] The ten point average roughness Rzjis on the surface of (methyl) acrylic resin film is preferably more than 5nm and below 100nm, more preferably more than 10nm and below 90nm.If the ten point average roughness Rzjis on the surface of (methyl) acrylic resin film is more than 5nm, then there is following tendency: when the optical film with easy bonding layer will be formed on (methyl) acrylic resin film is rolled into roll, even if the surface of easy bonding layer side overlaps with the surface on the opposite side of easy bonding layer, also can give play to anti-blocking property.In addition, if the ten point average roughness Rzjis on the surface of (methyl) acrylic resin film is below 100nm, then there is following tendency: the concavoconvex formed on the surface can not become too large, can prevent the functions such as the transparency of optical film from being affected, and, when optical film is rolled into roll, can prevent the surface of film from being damaged, concavoconvex defect.
[0124] The ten-point average roughness Rzjis of the surface of the (meth)acrylic resin film can be measured in accordance with JIS B0601:2013 using a laser microscope LEXT OLS5100 manufactured by Evident.
[0125] (additive)
[0126] The (meth)acrylic resin film may contain optional additives as needed. Examples of such additives include antioxidants; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; ultraviolet absorbers, flame retardants, antistatic agents, fillers, plasticizers, and lubricants.
[0127] (Thin Film Manufacturing Method)
[0128] The method for producing the (meth)acrylic resin film is not particularly limited, and methods such as injection molding, melt extrusion molding, inflation molding, blow molding, and compression molding may be employed. Alternatively, solution casting or spin coating methods may be employed, in which the (meth)acrylic resin is dissolved in a solvent and then formed. Of these, melt extrusion methods that do not use solvents are preferred. Melt extrusion methods can reduce manufacturing costs and reduce the burden of solvents on the global environment and the working environment.
[0129] The following describes an example of producing a (meth)acrylic resin film by melt extrusion. It should be noted that in the following description, films produced by melt extrusion are referred to as "melt-extruded films," as distinct from films produced by other methods such as solution casting.
[0130] When a (meth)acrylic resin film is produced by a melt extrusion method, first, a (meth)acrylic resin is supplied to an extruder and heated and melted.
[0131] The (meth)acrylic resin is preferably pre-dried before being supplied to the extruder. This pre-drying can prevent foaming of the resin extruded from the extruder. The pre-drying method is not particularly limited. For example, the raw material (such as the (meth)acrylic resin) can be pre-dried in a hot air dryer, vacuum dryer, or the like in a pelletized form.
[0132] Next, the (meth)acrylic resin, heated and melted in the extruder, is fed to the T-die through a gear pump, a filter, and the like. Using a gear pump tends to make the extrusion rate of the (meth)acrylic resin uniform, reducing thickness variations along the film's length. On the other hand, using a filter tends to remove foreign matter from the (meth)acrylic resin, resulting in a defect-free, excellent-looking (meth)acrylic resin film.
[0133] Next, the (meth)acrylic resin supplied to the T-die is extruded from the T-die as a sheet of molten resin. The sheet of molten resin is then clamped and cooled between two cooling rolls to form a film.
[0134] The two cooling rolls that sandwich the molten resin sheet are preferably: one a smooth, rigid metal roll, and the other a smooth, elastically deformable flexible roll with a metal elastic outer cylinder. By sandwiching the molten resin sheet between the rigid metal roll and the flexible roll with a metal elastic outer cylinder and cooling it to form a film, surface irregularities, die lines, and other defects can be corrected, resulting in a smooth film with a thickness variation of 5 μm or less. It should be noted that in this specification, the term "cooling roll" is used to encompass "touch rolls."
[0135] Even when using rigid metal rollers and flexible rollers, since the surfaces of both cooling rollers are metal, if the film is thin, there is a risk that the cooling rollers' surfaces may contact each other, causing damage to the outer surfaces of the cooling rollers or even damage to the cooling rollers themselves. Therefore, when forming a film using two cooling rollers to hold a sheet of molten resin, it is preferable to first hold the sheet of molten resin between the two cooling rollers and cool it to obtain a thicker raw film, and then uniaxially or biaxially stretch the raw film to produce a film of a predetermined thickness. For example, when producing a film with a thickness of 40 μm, it is preferable to first hold the sheet of molten resin between the two cooling rollers and cool it to obtain a 150 μm raw film, and then stretch the raw film by longitudinal and transverse biaxial stretching to produce a film with a thickness of 40 μm.
[0136] When the (meth)acrylic resin film is a stretched film, the stretched film can be produced by molding the (meth)acrylic resin into an unstretched raw film and then performing uniaxial stretching or biaxial stretching.
[0137] In order to improve the bending resistance of the (meth)acrylic resin film in both the longitudinal direction (MD direction) and the transverse direction (TD direction), it is preferable to perform biaxial stretching.
[0138] In this specification, for convenience of explanation, a film obtained by molding a (meth)acrylic resin into a film shape and before stretching, that is, a film in an unstretched state, is referred to as a "raw film."
[0139] When the blank film is stretched, the stretching may be performed continuously immediately after the blank film is formed, or the blank film may be stretched after being temporarily stored or moved after being formed.
[0140] It should be noted that when a raw film is stretched immediately after being formed, during the film manufacturing process, the raw film only needs to maintain a film shape sufficient for stretching, even for a very short time, and does not need to be in a perfect film state. Furthermore, the raw film does not need to have the properties of a finished film.
[0141] (Film stretching method)
[0142] The method for stretching the raw film is not particularly limited, and any conventionally known stretching method may be employed. For example, transverse stretching using a tenter, longitudinal stretching using rollers, or a combination of these methods, such as sequential biaxial stretching, may be employed. Furthermore, simultaneous biaxial stretching, which involves simultaneous longitudinal and transverse stretching, or a method in which longitudinal stretching using rollers followed by transverse stretching using a tenter may also be employed.
[0143] When stretching a raw film, it is preferred to preheat the raw film to a temperature 0.5°C to 5°C higher than the stretching temperature, preferably 1°C to 3°C higher, and then cool it to the stretching temperature before stretching. Preheating within this range tends to maintain the thickness of the raw film in the width direction with good accuracy, while also preventing a decrease in thickness accuracy or unevenness in the stretched film. This also tends to prevent the raw film from sticking to the rollers or sagging under its own weight.
[0144] The stretching temperature when the raw film is stretched is not particularly limited and can be appropriately determined according to the mechanical strength, surface properties, thickness accuracy, etc. required for the stretched film. Generally speaking, when the glass transition temperature of the raw film ((meth) acrylic resin composition) obtained by the DSC method is set to Tg, it is preferably set to a temperature range of (Tg-30°C) to (Tg+30°C), more preferably set to a temperature range of (Tg-20°C) to (Tg+30°C), further preferably set to a temperature range of (Tg) to (Tg+30°C), and particularly preferably set to a temperature range of (Tg+10°C) to (Tg+30°C). If the stretching temperature is within the above temperature range, there is a tendency to reduce the thickness unevenness of the resulting stretched film, and further, to improve the mechanical properties such as elongation, tear propagation strength, and MIT bending resistance. In addition, there is a tendency to prevent the occurrence of problems such as the film sticking to the roller.
[0145] The stretch ratio for stretching the raw film is not particularly limited and can be appropriately determined based on the mechanical strength, surface properties, and thickness accuracy of the stretched film. The stretch ratio, which also depends on the stretching temperature, is generally preferably selected within the range of 1.1 to 3 times, more preferably within the range of 1.3 to 2.5 times, and even more preferably within the range of 1.5 to 2.3 times. If the stretch ratio is within the above range, there is a tendency to significantly improve the film's mechanical properties, such as elongation, tear propagation strength, and rubbing fatigue resistance. Therefore, it is possible to produce stretched films with a thickness unevenness of less than 5 μm and an internal haze of less than 1.0%.
[0146] When the (meth)acrylic resin film contains a cross-linked elastomer, an unstretched film, a uniaxially stretched film, or a biaxially stretched film can be preferably used because the film has excellent mechanical strength.
[0147] The smaller the phase difference value of the (meth)acrylic resin film, the better. Preferably, the in-plane phase difference Δnd is less than 5.0 nm, and the thickness direction phase difference Rth is less than 20.0 nm. More preferably, Δnd is less than 2.0 nm, and Rth is less than 5.0 nm. Further preferably, Δnd is less than 1.0 nm, and Rth is less than 3.0 nm.
[0148] The thickness of the (meth)acrylic resin film is preferably from 5 μm to 200 μm, more preferably from 10 μm to 100 μm. When the thickness of the (meth)acrylic resin film is 5 μm or greater, sufficient strength tends to be achieved. Furthermore, when the thickness of the (meth)acrylic resin film is 200 μm or less, a decrease in transparency and a decrease in the drying properties of the adhesive solvent (e.g., water) tend to be suppressed, and the optical film can be made thinner.
[0149] The surface wetting tension of the (meth)acrylic resin film is preferably 40 mN / m or greater, more preferably 50 mN / m or greater. To increase the surface wetting tension, corona discharge treatment, plasma treatment, ozone treatment, ultraviolet irradiation, flame treatment, chemical treatment, etc. may be applied. Among these, corona discharge treatment and plasma treatment are preferred.
[0150] [Adhesive layer]
[0151] By forming an easy-adhesive layer on the surface of a (meth) acrylic resin film, the adhesion to the polarizer is greatly improved. The easy-adhesive layer can be formed by applying an easy-adhesive layer-forming composition on the surface of a (meth) acrylic resin film having uneven surfaces formed by compounding crosslinked particles and drying the composition. As a result, uneven surfaces of the easy-adhesive layer formed on the surface of the (meth) acrylic resin film also appear, and anti-blocking properties can be achieved (see Figure 1 ).
[0152] The content of the lubricating particles in the easy bonding layer is below 0.1 % by weight. Lubricating particles such as silicon dioxide particles are easily gathered in the easy bonding layer forming composition. Therefore, it is sometimes difficult to make lubricating particles evenly distributed on the surface of (methyl) acrylic resin film, and it is impossible to give full play to anti-blocking property. In addition, the aggregation of lubricating particles sometimes also affects the functions such as the transparency of optical film. Therefore, the content of the lubricating particles such as silicon dioxide particles in the easy bonding layer forming composition is set to below 0.1 % by weight, further preferably does not contain. It should be noted that lubricating particles refer to the particles giving anti-blocking property.
[0153] The content of lubricating particles in the adhesion layer can be determined, for example, by observing with a transmission electron microscope (TEM) to determine the number concentration, preparing several adhesion layers with a concentration close to that number concentration, and plotting a calibration curve for calculation.
[0154] The composition for forming an easy-adhesion layer applied to the surface of a (meth)acrylic resin film can be an aqueous composition or an organic composition. From the perspectives of environmental protection and workability, an aqueous composition for forming an easy-adhesion layer is preferred. From the perspectives of dispersibility and solubility, a small amount of an organic solvent may be contained. As the organic solvent, alcohol solvents, ketone solvents, ester solvents, and ether solvents are preferred from the perspectives of compatibility with water and ease of handling.
[0155] The easy bonding layer can be formed using the known technology described in Japanese Patent Application Publication No. 2009-193061, Japanese Patent Application Publication No. 2010-55062, etc. For example, the easy bonding layer forming composition comprising a carboxyl group-containing urethane resin and a cross-linking agent can be used to form it. By using urethane resin, the easy bonding layer with excellent adhesion of the polarizer can be obtained.
[0156] Before applying the easily-adhesive layer-forming composition, it is preferred that the surface of the (meth)acrylic resin film be subjected to a corona discharge treatment, a plasma treatment, or the like.
[0157] Any appropriate method can be used to apply the easily adhesive layer-forming composition, such as bar coating, roll coating, gravure coating, rod coating, slot die coating, curtain coating, or spray coating.
[0158] The drying temperature of the easily adhesive layer-forming composition is preferably 50° C. or higher, more preferably 80° C. or higher.
[0159] The Young's modulus of easy bonding layer can affect the static friction coefficient, and can affect anti-blocking property in the optical film described in the present embodiment.The Young's modulus of easy bonding layer is set to more than 1.0GPa and less than 2.5GPa.If the Young's modulus of easy bonding layer is more than 1.0GPa, then there is the tendency that can suppress the increase of static friction coefficient, can realize good anti-blocking property.In addition, if the Young's modulus of easy bonding layer is less than 2.5GPa, then there is the tendency that can give flexibility to optical film, the adhesion of polarizer improves.The Young's modulus of easy bonding layer is preferably more than 1.2GPa and less than 2.0GPa, more preferably more than 1.3GPa and less than 1.8GPa.
[0160] The Young's modulus of the easily adhesive layer can be measured by forming a sheet made of only the easily adhesive layer-forming composition so that the thickness of the sheet after drying becomes 100 μm, and measuring the Young's modulus by a tensile test according to JIS K 7161-2:2014.
[0161] The ten point average roughness Rzjis on the surface of easy bonding layer is preferably more than 18nm and below 100nm, more preferably more than 30nm and below 90nm.If the ten point average roughness Rzjis on the surface of easy bonding layer is more than 18nm, then there is the tendency that the surface concavo-convex of easy bonding layer becomes fully, can give play to anti-blocking property.In addition, if the ten point average roughness Rzjis on the surface of easy bonding layer is below 100nm, then there is following tendency: the concavo-convex formed on the surface can not be too large, can prevent the functions such as the transparency of optical film from being affected, and, when optical film is rolled into roll, can prevent the surface of film from being damaged, concavo-convex defect.
[0162] The ten-point average roughness Rzjis of the surface of the easily adhesive layer can be measured in accordance with JIS B 0601:2013 using a laser microscope LEXT OLS5100 manufactured by Evident.
[0163] The sum of the ten-point average roughness Rzjis of the surface of the easy-adhesion layer and the ten-point average roughness Rzjis of the surface of the (meth)acrylic resin film on the opposite side of the easy-adhesion layer is 23 nm to 200 nm, preferably 30 nm to 150 nm. If the sum of Rzjis is 23 nm or more, there is a tendency to ensure slippage. On the other hand, if the sum of Rzjis is 200 nm or less, there is a tendency to prevent the appearance of external haze due to surface irregularities, thereby deteriorating transparency.
[0164] The thickness of easy bonding layer is preferably more than 50nm and below 600nm.If the thickness of easy bonding layer is more than 50nm, then there is the tendency that the intensity of easy bonding layer improves, can improve adhesion.In addition, if the thickness of easy bonding layer is below 600nm, then there is following tendency: the concavo-convex that suppresses to be caused by the crosslinked particles that comprise in (methyl) acrylic resin film is because of easy bonding layer and smoothing, can guarantee anti-blocking property.
[0165] [use]
[0166] The optical film described in this embodiment is preferably a functional film used in various display devices such as liquid crystal displays, plasma displays, and organic EL displays, as well as touch panels. Specifically, the optical film described in this embodiment can be a polarizer protective film for liquid crystal displays, a retardation film, an antireflection film, a brightness enhancement film, a hard coat film, an antiglare film, an antistatic film, or an optical compensation film such as a viewing angle expansion film.
[0167] Example
[0168] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the following examples.
[0169] The measurement methods of various physical properties described in the Examples are as follows.
[0170] (Glass transition temperature)
[0171] The glass transition temperature was determined by a midpoint method using a differential scanning calorimeter (DSC7000X, manufactured by Hitachi High-Technologies Corporation) while heating at a heating rate of 20° C. / min in a nitrogen atmosphere.
[0172] (Young's modulus)
[0173] Young's modulus was measured by forming a sheet composed solely of the easily adhesive layer-forming composition and performing a tensile test in accordance with JIS K7161-2:2014. The easily adhesive layer-forming composition was formed by pouring an aqueous dispersion of polyurethane into a glass container to a film thickness of 100 μm after drying. The film was then allowed to stand at room temperature for 24 hours and then dried at 50°C for 3 hours and 120°C for 20 minutes.
[0174] (Surface roughness)
[0175] The surface roughness is measured in accordance with JIS B 0601:2013 using a laser microscope LEXTOLS5100 manufactured by Evident. A confocal image of the film in the range of 257μm×257μm is obtained using an objective lens with a magnification of 50 times and an aperture of 0.95. Next, three evaluation lines are drawn at equal intervals for the MD direction and the TD direction, and a roughness curve is extracted. Based on the obtained roughness curve, the ten-point average roughness Rzjis is calculated using analysis software, and the average value of the measurement position is calculated. The measurement position is changed 5 times during the measurement, and their average value is used as the surface roughness. Among them, when local abnormalities such as damage are clearly confirmed from the image, they are not used as the measurement value, and the abnormal part is avoided and re-measured.
[0176] (Static friction coefficient)
[0177] The static friction coefficient was measured according to JIS K 7125:1999. One film sheet was fixed to a smooth stainless steel plate, and the other film sheet was attached to a 60 mm x 60 mm, 200 g slider using double-sided tape. A load cell was then used to measure the load when the slider was moved at a speed of 20 mm / min via a pulley. The static friction coefficient was calculated. The measurement was repeated five times, varying the film sheet, and the average value was calculated.
[0178] (Adhesion test)
[0179] Ten 100 mm x 100 mm film sheets were placed with the substrate ((meth)acrylic resin film) surface in contact with the adhesive layer surface. A pressure of 1 kg was applied from above and the film was left at 60°C for 2 hours. The film was then naturally cooled at 23°C for 1 hour. The film condition was visually inspected and manually peeled off, and evaluated according to the following criteria.
[0180] -Evaluation Criteria-
[0181] A: No adhesion between the thin films was observed.
[0182] B: The films are fixed to each other.
[0183] C: The films were firmly adhered to each other, and there were traces of the films peeling off.
[0184] <Production Example 1: Production of (meth)acrylic resin>
[0185] As an extruder, a 40 mm diameter intermeshing co-rotating twin-screw extruder (L / D=90) was used. The set temperature of each temperature control zone of the extruder was set to 250°C to 280°C, and the screw speed was set to 85 rpm. After the polymethyl methacrylate resin was melted and filled with a kneading block, 1.8 parts by weight of monomethylamine (manufactured by Mitsubishi Gas Chemical Co., Ltd.) was injected with respect to 100 parts by weight of the polymethyl methacrylate resin. The resin extruded in the form of strands from the die set at the extruder outlet was cooled in a water tank and pelletized with a pelletizer to obtain resin (I). Subsequently, the set temperature of each temperature control zone of the 40 mm diameter intermeshing co-rotating twin-screw extruder was set to 240°C to 260°C, and resin (I) was supplied from a hopper. 0.56 parts by weight of dimethyl carbonate was injected from a nozzle with respect to 100 parts by weight of the polymethyl methacrylate resin to reduce the carboxyl groups in resin (I). Furthermore, the reaction byproducts and excess dimethyl carbonate were removed. The resin extruded from the die at the extruder outlet in the form of strands was cooled in a water tank and then pelletized using a pelletizer to obtain a (meth)acrylic resin having a glutarimide structure in its main chain. The resulting (meth)acrylic resin had a glass transition temperature of 123°C.
[0186] The ratio of the glutarimide unit in the obtained (meth)acrylic resin is calculated as follows. 1 H-NMR BRUKER Avance III (400 MHz) was used to analyze the (meth)acrylic resin. 1 H-NMR measurement was performed. The molar ratio was then calculated based on the peak area A of the protons originating from O-CH3 constituting methyl methacrylate near 3.5 ppm to 3.8 ppm and the peak area B of the protons originating from N-CH3 constituting the glutarimide ring near 3.0 ppm to 3.3 ppm. The molar ratio was converted to weight to calculate the proportion of glutarimide units. The result showed that the proportion of glutarimide units was 6% by weight. Hereinafter, the (meth)acrylic resin obtained in Production Example 1 will be referred to as "Resin 1."
[0187] <Example 1>
[0188] A mixture containing 99.9 parts by weight of the resin 1 produced in Production Example 1 and 0.1 parts by weight of cross-linked acrylic resin particles (MX80H3wT, manufactured by Soken Chemical Co., Ltd., refractive index: 1.49; hereinafter referred to as "pellets 1") having an average particle size of 0.8 μm was kneaded using a 15 mm diameter intermeshing co-rotating twin-screw extruder (L / D = 45). The resin extruded in the form of strands from a die located at the extruder outlet was cooled in a water tank and then pelletized using a pelletizer to obtain a (meth)acrylic resin composition (refractive index: 1.49).
[0189] The resulting (meth)acrylic resin composition was dried at 100°C for 5 hours and then formed into a film using an intermeshing, co-rotating twin-screw extruder (L / D = 45) equipped with a 15 mm diameter T-die at the extruder outlet. The sheet of molten resin extruded from the T-die at the extruder outlet was cooled using a chill roll to produce a raw film having a width of 160 mm and a thickness of 160 μm. The surface in contact with the casting roll was designated as surface B, and the other surface as surface A. The glass transition temperature of the raw film was 123°C.
[0190] The B side of the raw film was subjected to corona discharge treatment (corona discharge electron irradiation dose: 100 W / m 2 / min). 5 g of a water-based urethane resin having a carboxyl group (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content: 35%) and 1 g of a crosslinking agent (manufactured by Nippon Shokubai Co., Ltd., solid content: 25%) were added to 26 g of pure water and stirred for 3 minutes to prepare a composition for forming an easy-adhesion layer. The obtained composition for forming an easy-adhesion layer was applied to the corona discharge-treated surface of the raw film that had been subjected to corona discharge treatment using a bar coater (line number #10). Thereafter, the raw film was placed in a hot air dryer (100°C) and dried for 3 minutes to obtain an easy-adhesion-treated film.
[0191] The obtained adhesion-improving treated film was simultaneously biaxially stretched using a biaxial stretching apparatus (IMC-1905, manufactured by Imoto Seisakusho Co., Ltd.) at a stretching ratio of 2 (vertical and transverse) and at 145° C. to produce an optical film.
[0192] <Example 2>
[0193] An optical film was produced in the same manner as in Example 1 except that a (meth)acrylic resin composition containing 99.8 parts by weight of the resin and 0.2 parts by weight of the particles was used to produce a raw film and the thickness of the easily adhesive layer was changed.
[0194] <Example 3>
[0195] An optical film was produced in the same manner as in Example 2 except that the thickness of the easily adhesive layer was changed.
[0196] <Example 4>
[0197] An optical film was produced in the same manner as in Example 2 except that the thickness of the easily adhesive layer was changed.
[0198] <Example 5>
[0199] An optical film was produced in the same manner as in Example 2 except that the type of the water-based urethane resin forming the easy-adhesion layer was changed.
[0200] <Comparative Example 1>
[0201] An optical film was produced in the same manner as in Example 2 except that the particles 1 were not added to the raw film.
[0202] <Comparative Example 2>
[0203] An optical film was produced in the same manner as in Example 2 except that the type of the water-based urethane resin forming the easy-adhesion layer was changed.
[0204] <Comparative Example 3>
[0205] An optical film was produced in the same manner as in Example 2 except that the type of the water-based urethane resin forming the easy-adhesion layer was changed.
[0206] <Reference Example 1>
[0207] An optical film was produced in the same manner as in Example 2 except that 20% by weight of silica particles (colloidal silica, manufactured by Fuso Chemical Industries, Ltd., QUARTRON PL-3, solid content: 20%) were added to the easily adhesive layer.
[0208] <Example 6>
[0209] An optical film was produced by the same procedure as in Example 1 except that a (meth)acrylic resin composition containing 79.9 parts by weight of resin 1, 20 parts by weight of a methyl methacrylate-styrene copolymer (MS-750 manufactured by Toyo Styrene Co., Ltd.; hereinafter referred to as "resin 2") having a styrene unit ratio of 25% and 0.1 parts by weight of particles 1 was used to produce a raw film. The thickness of the easy-adhesive layer was changed, and the optical film was produced.
[0210] <Example 7>
[0211] An optical film was produced in the same manner as in Example 6 except that the type of the water-based urethane resin forming the easy-adhesion layer was changed.
[0212] <Example 8>
[0213] An optical film was obtained in the same manner as in Example 6 except that Particles 1 were replaced with crosslinked acrylic resin particles having an average particle size of 2.2 μm (J-4PY manufactured by Negami Industry Co., Ltd., refractive index: 1.49; hereinafter referred to as “Particles 2”).
[0214] <Example 9>
[0215] An optical film was obtained in the same manner as in Example 7 except that Particles 1 were changed to Particles 2.
[0216] <Comparative Example 4>
[0217] An optical film was produced in the same manner as in Example 6 except that the type of the water-based urethane resin forming the easy-adhesion layer was changed.
[0218] <Reference Example 2>
[0219] An optical film was produced in the same manner as in Example 6 except that 20% by weight of silica particles (colloidal silica, manufactured by Fuso Chemical Industries, Ltd., QUARTRON PL-3, solid content: 20%) were added to the easily adhesive layer.
[0220] <Reference Example 3>
[0221] An optical film was obtained in the same manner as in Reference Example 2 except that Particles 1 were changed to Particles 2.
[0222] The evaluation results based on the blocking test are shown in Tables 1 and 2 together with the values of the glass transition temperature, Young's modulus, surface roughness, and static friction coefficient measured according to the above-mentioned methods.
[0223] In Table 1 and Table 2, the resins forming the easy-adhesion layer are as follows.
[0224] Resin A: Urethane resin (SUPERFLEX 210, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and crosslinking agent (EPOCROS WS700, manufactured by Nippon Shokubai Co., Ltd.)
[0225] Resin B: Urethane resin (Superflex 870, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)
[0226] Resin C: Urethane resin (Superflex 150, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)
[0227] Resin D: Urethane resin (Superflex 460S, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) [Table 1]
[0228]
[0229] [Table 2]
[0230]
[0231] As shown in Tables 1 and 2, Examples 1 to 9 have appropriate irregularities on the easily adhesive surface, resulting in an appropriate surface roughness. This reduces the coefficient of friction between the substrate and the easily adhesive layer when the optical film is rolled. The evaluation results in Tables 1 and 2 confirm that the films exhibit anti-blocking properties.
Claims
1. An optical film comprising a (meth)acrylic resin film and an easy-adhesion layer formed on the (meth)acrylic resin film, wherein the (meth)acrylic resin film contains a (meth)acrylic resin as a main component and crosslinked particles, wherein the optical film satisfies the following conditions: (i) the glass transition temperature of the (meth)acrylic resin film is 120° C. or higher, (ii) the Young's modulus of the composition for forming the easily adhesive layer when formed into a sheet having a thickness of 100 μm is 1.0 GPa or more and 2.5 GPa or less, (iii) the content of the lubricating particles in the easy-adhesion layer is 0.1% by weight or less, (iv) The total value of the ten-point average roughness Rzjis of the surface of the easily adhesive layer and the ten-point average roughness Rzjis of the surface of the (meth)acrylic resin film on the opposite side to the easily adhesive layer is 23 nm to 200 nm.
2. The optical film according to claim 1, wherein The thickness of the easy-adhesion layer is 50 nm to 600 nm.
3. The optical film according to claim 1 or 2, wherein: When two optical films are stacked such that the (meth)acrylic resin film is in contact with the easily adhesive layer, the static friction coefficient measured in accordance with JIS K 7125:1999 is 0.3 or more and 1.5 or less.
4. The optical film according to claim 1 or 2, wherein The (meth)acrylic resin film includes a (meth)acrylic resin having a ring structure in its main chain.
5. The optical film according to claim 4, wherein The ring structure is at least one selected from the group consisting of a glutarimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure.
6. The optical film according to claim 4, wherein The (meth)acrylic resin having a ring structure in the main chain includes a structural unit represented by the following general formula (1): In formula (1), R 1 and R 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
7. The optical film according to claim 6, wherein The ratio of the structural unit represented by the general formula (1) in the (meth)acrylic resin having a ring structure in the main chain is 2% by weight or more and 30% by weight or less.
8. The optical film according to claim 1, wherein The (meth)acrylic resin film includes an aromatic vinyl unit.
9. The optical film according to claim 4, wherein The (meth)acrylic resin film further includes a copolymer containing an aromatic vinyl unit.
10. The optical film according to claim 8, wherein The copolymer further comprises (meth)acrylate units or (meth)acrylonitrile units.
11. A composition for forming an easily adhesive layer, for forming an easily adhesive layer on a (meth)acrylic resin film. The (meth)acrylic resin film comprises a (meth)acrylic resin as a main component, contains crosslinked particles, and has a glass transition temperature of 120° C. or higher. The content of the lubricating particles in the easily adhesive layer-forming composition is 0.1% by weight or less. The Young's modulus of the easily-adhesive layer-forming composition when formed into a sheet having a thickness of 100 μm is 1.0 GPa or more and 2.5 GPa or less.
Citation Information
Patent Citations
JP1977032665B2
Preparation of polymer particle containing little foreign matter
JP1981008404A
Novel method for producing methacrylic polymer
JP1994086492B2
Method for producing methacrylic polymer
JP1995037482B2
Manufacturing method for thermoplastic resin, and thermoplastic resin
JP2008273140A